Total Water Column Analysis Shows the Importance of a Single Species in Subsurface Chlorophyll Maximum Thin Layers in Stratified Waters - Barnett, Michelle L.; Kemp, Alan E. S.; Nimmo-Smith, W. Alex M.; Purdie, Duncan A. (Frontiers in Marine Science, 2022)
Marine phytoplankton form the base of marine food webs and are the driving force of the marine carbon cycle, so understanding the dynamics of their blooms is critical. While near-surface marine productivity (<10 m water depths) is extensively documented, that of the subsurface is less well characterised. Increasing evidence of the importance of subsurface chlorophyll maxima (SCM) and climatically driven increases in stratification of surface waters that promote SCM development call for improved sampling of the subsurface. To address this, we targeted the summer stratified waters of the Western English Channel, part of the NW European shelf seas, where SCM are commonly developed. In situ holography was applied to undertake the highest ever resolution, total water column, quantitative analysis of microplankton distribution, and demonstrated the importance of a SCM, collocated with the thermocline, dominated by a single species, the dinoflagellate Ceratium fusus. This species was dominant in the SCM over a wide area of the NW European shelf in the June/ July 2015 study period and comprised up to 85% of the SCM biomass. Analysis of similarity and multivariate non-metric multidimensional scaling showed the phytoplankton community of the SCM to be statistically distinct from those of the surface and deep waters. Holography also revealed a fine scale layering of taxa at different levels within the SCM, likely reflecting ecological differences. Some taxa followed the peak abundance of C. fusus, while others reached maximum abundances immediately below or above the C. fusus maximum, suggesting the possible operation of exclusion mechanisms. Additionally, the detection of abundant aggregates located only within and beneath the SCM demonstrates the potential importance of this deep production for the export of carbon to the sea floor. Some predictions of phytoplankton productivity propose a shift to smaller cells in the more stratified oceans of the future resulting in declining production and export. Results presented here, however, contribute to a growing body of evidence that suggests, on the contrary, that key species among the larger celled/ colonial, SCM-adapted diatoms and dinoflagellates may instead be selected in stratified conditions, driving increased production and export.